Post-crisis monetary policy and social cohesion - Jacek Tomkiewicz (Transformation, Integration and Globalization Economic Research (TIGER), 2014)
Goal of the text is show that although non-standard monetary policy conducted by major central banks is quite efficient in stabilizing post-crisis economy, there are few important side effects of such policy. One of the most important side effect of superexpansionary monetary policy is creating economic environment which favours financial sector and capital owners over working class what leads to higher income inequalities. Low level of central banks' interest rate does not mean that every economic unit has access to cheap capital. Ultra low cost of capital can be experienced only by the few selected players - financial institutions and strong corporations. The same can be said about the financing borrowing needs of the state - only few governments are able to borrow very cheap and others have to face huge power of financial market what leads to growing income gap between societies.
Keywords: E63; E64; F2; 330; financial crisis; macroeconomic policy; social cohesion